A Rare Fish Amphistome Revisited: The Phylogenetic Position of Kalitrema kalitrema (Trematoda: Cladorchiidae) Found in Hypostomus spp. (Siluriformes: Loricariidae) from Brazil - Pinto, Hudson Alves; Pantoja, Camila; Assis, Jordana Costa Alves de; López-Hernández, Danimar; Vieira, Fabio; Luque, José Luis; Alves, Philippe Vieira [UNESP] (MDPI, 2023)
Despite recent advances in the molecular knowledge of amphistome trematodes, most genera known from fish remain to be genetically characterized. This is the case for Kalitrema, a genus of the speciose family Cladorchiidae and the type of Kalitrematinae. The type and only species of this genus, Kalitrema kalitrema Travassos, 1933, was originally proposed based on two specimens found in an armored suckermouth catfish from Brazil, and its phylogenetic position has not been evaluated. In this study, paramphistomes found in Hypostomus alatus (2/9; 22.2%) and Hypostomus francisci (4/143; 2.8%) from the Paraobepa River (São Francisco River basin), Minas Gerais, Brazil, between December 2019 and November 2021, were subjected to morphological study. The parasites were identified in low intensity of infection [1.2 (1–2)] and redescribed as K. kalitrema. This species exhibits unique features such as a linguiform body with a circular ridge near the anterior end and a deep, median notch present at the posterior extremity of the body, apparently dividing the body into two lobes. A subset of specimens was further subject to phylogenetic analyses based on the most densely sampled markers, the nuclear ribosomal RNA (28S and ITS2) and mitochondrial cox1, which revealed the inclusion of K. kalitrema in a Neotropical clade of fish paramphistomes. The most comprehensive phylogenetic tree, based on the 28S dataset, confirmed K. kalitrema as an independent, early diverging lineage among Neotropical fish cladorchiids. However, the monophyly of Kalitrematinae was not sustained, given that species of the other kalitrematine genera Pseudocladorchis and Iquitostrema included in the phylogenetic analysis fell in a distinct clade with other fish cladorchiids. As a result, we propose here a narrower concept for Kalitrematinae sensu stricto, accommodating only Kalitrema (type genus) until a more natural subfamilial or familial classification is provided.
Keywords: cladorchiids; fish paramphistomes; integrative taxonomy; Paramphistomoidea; systematics